Joining structure of dissimilar metal plates
Patent Information
- Application Number
- JP2025062481
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0020】 本発明によれば、板厚比が大きいチタン板とチタン以外の金属板との接合構造物であって、簡便に製造することができ、接合強度に優れた新規な接合構造物を提供することができる。
Smart Images

Figure 2026168920000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a joined structure of dissimilar metal plates, specifically to a joined structure of a titanium plate and a metal plate other than titanium.
Background Art
[0002] Titanium is used in a wide range of fields due to its excellent specific strength, corrosion resistance, light weight, workability and the like. For example, titanium is used as a coating material for coating the inner surfaces of tanks and distillation columns in chemical plants or the outer surfaces of marine structures. By coating the surface of a steel structure with titanium in this manner, a steel structure having excellent specific strength and corrosion resistance can be formed.
[0003] On the other hand, when titanium and an iron-based material (for example, steel, SUS, etc.) are welded by resistance spot welding or the like, an intermetallic compound of titanium and iron may be formed at the joining interface of the welded portion. Since intermetallic compounds are extremely brittle, if such an intermetallic compound is formed at the joining interface, the strength of the joined portion decreases, which may make it difficult to obtain practical strength.
[0004] Therefore, at present, a method of manufacturing a structure using a titanium clad steel sheet produced by an explosive welding method or a roll rolling method, and coating the surface of the structure with titanium, and the like are adopted. In this method, it is necessary to perform welding on the steel sheet side and welding on the titanium sheet side separately at the joint between the clad steel sheets, so as to prevent the formation of brittle iron-titanium intermetallic compounds in the welded portion on the titanium sheet side, which makes the joining work process complicated.
[0005] In addition to the above, various methods for joining titanium and iron-based materials are known. For example, Patent Document 1 discloses a method of overlapping and joining a titanium plate and a steel plate, in which a low-carbon insert steel material is interposed on the steel plate side and a low-carbon stainless steel mesh insert material is interposed on the titanium plate side, and a copper plate is placed between the titanium plate and an electrode to perform resistance welding. In this Patent Document 1, the joining method involves inserting a low-carbon stainless steel mesh and a low-carbon insert steel material, and performing resistance welding under appropriate welding conditions where the welding current is appropriate for the electrode width or diameter, thereby preventing the formation of brittle carbides at the joint.
[0006] Furthermore, Patent Document 2 discloses a joining structure between steel and a titanium plate with a thickness of 2 mm or less, wherein the joining structure is a lap resistance welding joining structure, and the proportion of the joining interface between the titanium plate and steel at the joining portion where the thickness of the intermetallic compound layer is 10 μm or less is 50% or more. The joining structure described in Patent Document 2 is obtained by forming irregularities on one or both surfaces of the steel and titanium plates before joining, overlapping the steel and titanium plates on the surfaces with the irregularities, and melting the interface by overlap resistance welding. The joining structure described in Patent Document 2 is said to have excellent resistance to embrittlement.
[0007] Furthermore, Patent Document 3 discloses a method for joining metal materials, in which a spot load is applied to the joint portion of a first metal material and a second metal material by a pressurizing means while the joint portion of the two metal materials is overlapped, and if the total thickness of the first and second metal materials at the joint portion is T0 mm before joining and T1 mm after joining, the reduction ratio R = T0 / T1 is 1.8 or more, and by applying a spot load to the joint portion with a pressurizing means, plastic flow occurs at the joint interface, and solid-phase diffusion bonding is achieved at a low temperature, the pressurizing means for applying the spot load is punch-shaped with a circumscribed circle diameter of 3 to 15 mm, the bonding temperature for solid-phase diffusion bonding at a low temperature is in the range of 270 to 450°C, and the thickness of the IMC (intermetallic compound) generated at the joint interface of the joint portion is less than 1 μm. The joining method described in Patent Document 3 involves preheating the joint before applying a spot load, and then applying a spot load to the joint using a pressurizing means. This causes plastic flow to occur at the joint interface from the pressurized area toward the surrounding area, resulting in the appearance of a new surface, which is then joined by solid phase diffusion on this new surface. This joining method described in Patent Document 3 is said to have superior strength and high productivity by suppressing the formation of IMC at the joint. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 7-266058 [Patent Document 2] Patent No. 4216980 [Patent Document 3] Patent No. 7526404 [Overview of the Initiative] [Problems that the invention aims to solve]
[0009] However, the conventional joining methods described above have room for improvement in terms of simplicity and joint strength. For example, the joining method described in Patent Document 1 requires the insertion of two types of insert materials between the titanium plate and the steel plate, and the placement of a copper plate between the titanium plate and the electrode, making the joining process complicated. Furthermore, the need for various insert materials and auxiliary materials such as copper plates raises concerns about increased manufacturing costs.
[0010] Furthermore, the joining structure described in Patent Document 2 requires the formation of irregularities on one or both surfaces of the steel and titanium plates before joining, making the joining process complicated. In addition, because the interface is melted during joining, there are limitations to suppressing intermetallic compounds, and there is a risk that the desired joint strength may not be achieved.
[0011] Furthermore, the joining method described in Patent Document 3 requires preheating of the joint before applying a spot load, making the joining process complicated. Also, when using two metal materials with a large thickness ratio, the difference in thickness may prevent an appropriate joining temperature from being obtained at the joining interface, potentially leading to a poor joint and failing to achieve the desired joint strength. In this specification, a "large thickness ratio" is sometimes used when the thickness of one metal material is four times or more that of the other metal material.
[0012] In addition to the joining methods described above, other joining methods such as mechanical joining, brazing, and friction joining are also possible. However, these joining methods also involve complicated joining processes, and there is a risk that the desired joint strength may not be achieved.
[0013] This invention has been made in view of the above circumstances, and aims to provide a novel joining structure for a titanium plate with a large thickness ratio and a metal plate other than titanium, which can be easily manufactured and has excellent joining strength. [Means for solving the problem]
[0014] The present invention includes the following embodiments.
[0015] (Aspect 1) A joint structure between a titanium plate and a metal plate other than titanium, The above-mentioned joint structure has point joints between the titanium plate and the metal plate, The thickness of the above metal plate is four times or more the thickness of the above titanium plate. A jointed structure characterized in that, at the joint interface between the titanium plate and the metal plate at the point joint, the proportion of intermetallic compound layers with a thickness of 1 μm or less is 50% or more.
[0016] (Aspect 2) The joint structure according to embodiment 1, characterized in that, at a depth of 0.05 mm from the joint interface of the titanium plate, the maximum hardness within the joint region of the point joint is 15% or more higher than the average hardness of the base material of the titanium plate.
[0017] (Aspect 3) The joint structure according to embodiment 1 or 2, characterized in that the thickness of the titanium plate is 2.0 mm or less.
[0018] (Aspect 4) A joint structure according to any one of the above embodiments 1 to 3, characterized in that, at the above joint interface, one of the metal materials, either the titanium plate or the metal plate, protrudes 50 μm or more into the other metal material.
[0019] (Aspect 5) The joined structure according to any one of the above aspects 1 to 4, wherein a resin is interposed between the titanium plate and the metal plate.
Effects of the Invention
[0020] According to the present invention, it is possible to provide a novel joined structure which is a joined structure of a titanium plate having a large thickness ratio and a metal plate other than titanium, can be easily manufactured, and has excellent joining strength.
Brief Description of the Drawings
[0021] [Figure 1] Figure 1 is a cross-sectional view schematically showing a joined structure according to one embodiment of the present invention. [Figure 2] Figure 2 is a cross-sectional view schematically showing a state during joining of the joined structure of the present embodiment. [Figure 3] Figure 3 is an optical microscope photograph of a cross section of a joined structure which is an example of the present embodiment.
Modes for Carrying Out the Invention
[0022] Hereinafter, preferred embodiments of the joined structure of the present invention will be described in detail with reference to the drawings.
[0023] In order to achieve the above object, the present inventors have conducted intensive studies focusing on the joining method and joining conditions for dissimilar metal plates. As a result, the present inventors have found that when joining a titanium plate having a large thickness ratio and a metal plate other than titanium, solid-state joining is performed under specific joining conditions using an electrode having a specific electrode tip shape, thereby suppressing the formation of intermetallic compounds and enabling joining with high joining strength. This method does not require additional steps such as a treatment step before joining, and also does not require auxiliary materials such as insert materials. Therefore, even when joining a titanium plate having a large thickness ratio and a metal plate other than titanium, the joining can be easily performed, and a joined structure having excellent joining strength can be obtained.
[0024] The present invention was completed based on these findings and includes the following embodiments.
[0025] Hereinafter, preferred embodiments of the joint structure of the present invention will be described in detail with reference to the drawings. Figure 1 is a schematic cross-sectional view showing a joint structure according to one embodiment of the present invention.
[0026] [Joined structure] As shown in Figure 1, a joint structure 1, which is one embodiment of the present invention, is a joint structure between a titanium plate 2 and a metal plate 3 other than titanium. The joint structure 1 of this embodiment has point joints 4 between the titanium plate 2 and the metal plate 3. Furthermore, in the joint structure 1 of this embodiment, the thickness of the metal plate 3 is four times or more the thickness of the titanium plate 2, and it is formed by a plate assembly with a large thickness ratio.
[0027] Furthermore, the joint structure 1 of this embodiment has a characteristic configuration in which the proportion of the intermetallic compound layer with a thickness of 1 μm or less at the joint interface between the titanium plate 2 and the metal plate 3 of the point joint portion 4 is 50% or more.
[0028] (Effects and Benefits) Generally, the intermetallic compound (IMC) layer formed at the joint interface is very brittle, and as its thickness increases, the overall brittleness of the joint increases. This makes the joint more susceptible to failure under external forces. In addition, a thick IMC layer is prone to stress concentration, which can lead to premature failure of the joint. Furthermore, as the IMC layer thickens, non-uniform structures and defects are more likely to occur within it, which can lead to a decrease in joint strength.
[0029] For the reasons stated above, when the IMC layer is thick, specifically when the IMC layer is 2 μm or thicker, cracks are more likely to occur and propagate in the IMC layer, which may significantly reduce the bonding strength.
[0030] On the other hand, as in the joint structure 1 of this embodiment, if the IMC layer is formed but its thickness is thin, such as 1 μm or less, the joint becomes a more uniform structure, resulting in a better stress distribution, thus reducing brittleness and increasing strength. As a result, crack propagation at the joint interface is suppressed, and when fracture occurs, it is more likely to occur within one of the plate materials. In other words, when the IMC layer is thin, the occurrence and propagation of cracks in the IMC layer are less likely to occur, and excellent joint strength can be achieved.
[0031] Furthermore, in the joint structure 1 of this embodiment, when joining a titanium plate 2 and a metal plate 3 having a large plate thickness ratio, i.e., a plate thickness ratio of four times or more, an electrode having a specific electrode tip shape as described later is used, and the joint structure is manufactured by solid-state bonding under specific bonding conditions. As a result, the formation of intermetallic compounds is suppressed in the joint structure 1 of this embodiment, and therefore high bonding strength can be achieved.
[0032] Furthermore, the manufacturing method for the joint structure 1 of this embodiment does not require additional processes such as pre-joining processing steps, nor does it require auxiliary materials such as insert materials. Therefore, even joint structures made of titanium plates with a large thickness ratio and metal plates other than titanium can be easily manufactured.
[0033] The components of the joint structure 1 of this embodiment will be described in more detail below.
[0034] (Titanium plate) In this embodiment, the titanium plate is not particularly limited as long as it is a plate material mainly composed of titanium, and for example, a plate material of titanium-based metal material such as pure titanium or titanium alloy can be used.
[0035] The thickness of the titanium plate can be any thickness depending on the structure to which the joint structure 1 of this embodiment is applied. For example, the thickness of the titanium plate may be 0.1 mm or more, 0.2 mm or more, 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, 0.7 mm or more, 1.0 mm or more and 1.2 mm or more, or 1.5 mm or more. Alternatively, the thickness of the titanium plate may be 12.0 mm or less, 10.0 mm or less, 8.0 mm or less, 6.0 mm or less, 5.0 mm or less, 4.0 mm or less, 3.0 mm or less, or 2.0 mm or less.
[0036] The shape of the titanium plate can be determined according to the shape of the structure to which the joint structure 1 of this embodiment is applied. That is, the shape of the titanium plate may be flat, or it may be molded into a predetermined shape.
[0037] (Metal plates other than titanium) In this embodiment, the metal sheet other than titanium is not particularly limited as long as it is a sheet material mainly composed of a metal other than titanium. For example, sheet materials of metal materials such as iron-based metal materials, aluminum-based metal materials, copper-based metal materials, nickel-based metal materials, zirconium-based metal materials, niobium-based metal materials, tantalum-based metal materials, and hafnium-based metal materials can be used.
[0038] Examples of iron-based metal materials include pure iron, steel, alloy steels such as stainless steel (SUS), and carbon steel. Alloy steels and carbon steels can be any material as long as iron is the main component. Specific examples of stainless steel include martensitic stainless steel, ferritic stainless steel, austenitic stainless steel, austenitic-ferritic duplex stainless steel, and precipitation-hardening stainless steel.
[0039] Examples of aluminum-based metal materials include pure aluminum, aluminum alloys such as the 1000 series, 2000 series, 3000 series, 4000 series, 5000 series, 6000 series, 7000 series, and 8000 series, as well as die-cast materials such as ADC1, ADC3, ADC5, ADC6, ADC10, ADC12, and ADC14.
[0040] Examples of copper-based metal materials include pure copper and copper alloys. Examples of nickel-based metal materials include pure nickel, nickel alloys, and Hastelloy®. Examples of zirconium-based metal materials include pure zirconium and zirconium alloys. Examples of niobium-based metal materials include pure niobium and niobium alloys. Examples of tantalum-based metal materials include pure tantalum and tantalum alloys. Examples of hafnium-based metal materials include pure hafnium and hafnium alloys.
[0041] If a sheet of iron-based metal material other than titanium is used, the surface may be plated with zinc or other plating treatments.
[0042] The thickness of the metal plate other than titanium can be set to a thickness appropriate to the structure to which the joint structure 1 of this embodiment is applied, as long as the thickness is four times or more the thickness of the titanium plate. For example, the thickness of the metal plate other than titanium may be 6.0 mm or more, 8.0 mm or more, 10.0 mm or more, 15.0 mm or more, 20.0 mm or more, 25.0 mm or more, or 30.0 mm or more. Alternatively, the thickness of the metal plate other than titanium may be 1500 mm or less, 1200 mm or less, 1000 mm or less, 800 mm or less, 500 mm or less, 300 mm or less, 100.0 mm or less, 80.0 mm or less, or 60.0 mm or less.
[0043] As mentioned above, the thickness ratio of non-titanium metal plates to the thickness of titanium plates is more than four times. In the case of plate assemblies with such a large thickness ratio, it is difficult to properly join them using conventional resistance spot welding because heat generation occurs on the thicker plate side. However, in this embodiment, by using an electrode with a specific electrode tip shape described later and performing solid-phase joining under specific joining conditions, the formation of intermetallic compounds can be suppressed, and a high joint strength can be achieved.
[0044] Therefore, in the present embodiment, the plate thickness ratio of the plate assembly may be 5 times or more, 8 times or more, 10 times or more, 12 times or more, or 15 times or more. On the other hand, the upper limit of the plate thickness ratio is not particularly limited, but from the viewpoint of ease of joining using electrodes and the like, it is, for example, 50 times.
[0045] The shape of the metal plate other than titanium can be a shape corresponding to the shape of the structure to which the joined structure of the present embodiment is applied. That is, the shape of the metal plate may be a flat shape, or may be formed into a predetermined shape.
[0046] Further, in the joined structure 1 of the present embodiment, the above-described titanium plate 2 and the metal plate 3 other than titanium are joined by spot joints 4 formed by a joining method described later.
[0047] (Thickness of intermetallic compound layer at joining interface) The joined structure 1 of the present embodiment has a characteristic configuration in which the proportion of the intermetallic compound layer (IMC layer) with a thickness of 1 μm or more at the joining interface between the titanium plate 2 and the metal plate 3 of the spot joint 4 is 50% or more. Thereby, in the joined structure 1 of the present embodiment, cracks are less likely to initiate and propagate in the IMC layer, and excellent joining strength can be exhibited.
[0048] Note that the condition that the thickness of the IMC layer is 1 μm or less includes the case where the thickness of the IMC layer is 0 μm, that is, the case where no IMC layer is formed at the joining interface of the spot joint.
[0049] The proportion of the IMC layer with a thickness of 1 μm or less at the joining interface of the joined structure can be measured by the following measurement method.
[0050] <Measurement method for the proportion of the IMC layer with a thickness of 1 μm or less> First, the joint structure to be measured is cut along the thickness direction, passing through the center of the point joint, to expose the cross-section of the joint structure. This cross-section is polished and etched, and then observed using a scanning electron microscope (SEM) as the observation surface. At this time, the parts of the metal plate other than titanium (e.g., steel) are observed as a clearly etched crystalline structure. On the other hand, the parts of the titanium plate and the IMC layer do not show an etched structure. The parts of the titanium plate and the IMC layer are distinguished by the difference in brightness.
[0051] Then, from the magnified image of the observation surface obtained by SEM, the length of the entire joint interface (i.e., the length of the portion where the titanium plate and the metal plate are in contact) and the length of the IMC layer with a thickness of 1 μm or less (including the interface portion where the IMC layer is not formed) are measured at the joint interface between the titanium plate and the metal plate at the point joint. By dividing the length of the IMC layer measured in this way by the length of the entire joint interface and multiplying by 100, the percentage (%) of the joint interface of the joint structure where the thickness of the IMC layer is 1 μm or less is calculated.
[0052] If the IMC layer with a thickness of 1 μm or less is not formed continuously along the bonding interface (i.e., it is formed intermittently and separately), the total length of these intermittent layers shall be considered the length of the IMC layer with a thickness of 1 μm or less.
[0053] In the joint structure 1 of this embodiment, the percentage of joints at the joint interface of the point joint 4 where the thickness of the IMC layer is 1 μm or less is preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and particularly preferably 100%. A percentage of 100% where the thickness of the IMC layer is 1 μm or less means that the thickness of the IMC layer is 1 μm or less across the entire joint interface of the point joint.
[0054] The joint structure 1 of this embodiment is manufactured by solid-phase bonding using electrodes having a specific electrode tip shape as described below, under specific bonding conditions. Here, Figure 2 is a schematic cross-sectional view showing the state of the joint structure of this embodiment during bonding.
[0055] The joint structure 1 of this embodiment is manufactured as follows. First, as shown in Figure 2, a plate assembly is formed by overlapping a titanium plate 2 with a large thickness ratio and a metal plate 3 made of a metal other than titanium. Next, the area to be joined in the plate assembly is clamped between a pair of electrodes, consisting of a first electrode 51 and a second electrode 52 that face each other, and current is applied. The resistive heat generated during this current application heats the area to be joined to a degree that does not melt the metal materials, thereby softening the interface between the titanium plate 2 and the metal plate 3.
[0056] Then, in parallel with or after heating the area to be joined, the area to be joined is locally pressurized with a pair of electrodes, applying a large load. As a result, the interface expands at the joining interface, destroying and refining impurity layers such as oxide films, while the metal materials are brought into contact with each other, causing diffusion and thus joining.
[0057] The pair of electrodes used in the above manufacturing method, namely the first electrode 51 and the second electrode 52, have a specific pointed shape, as shown in Figure 2, such that the tip is most convex, causing stress to be concentrated at the center of the joint. By giving the electrode tip such a shape, even when the plate thickness ratio is large, the current path can be concentrated at the joint interface, making it easier to cause resistive heating at the joint interface. In addition, since a large load can be concentrated at the joint center 4C, impurities at the joint interface can be broken down and refined more easily.
[0058] Furthermore, the pair of electrodes are not particularly limited in terms of material or structure other than the electrode tip shape, as long as they have the specific electrode tip shape described above. For example, the pair of electrodes may be copper electrodes such as tungsten copper, chromium copper, or zirconium copper, or tungsten electrodes or electrodes combining tungsten and copper electrodes may be used. By varying the tip shapes of the upper and lower electrodes in relation to the plate thickness of each material, more optimal pressure can be applied, enabling good bonding. In other words, the tip shapes of the upper and lower electrodes may be different from each other.
[0059] Furthermore, in the above manufacturing method, when applying current to the joint of the plate assembly by clamping it with a pair of electrodes, it is necessary to adjust the current application time and current to heat the surface of the titanium plate and the metal plate on the joint interface side to a temperature that does not melt the metal material at the interface. The surface temperature at this time depends on the type and thickness of each metal material in the plate assembly, but for example, it is between 350°C and 950°C.
[0060] Furthermore, in the above manufacturing method, when locally pressurizing the area to be joined with a pair of electrodes, it is necessary to adjust the pressurizing speed and the amount of indentation (maximum load) to apply a load to the joining interface that is suitable for breaking down and refining impurity layers such as oxide films at the joining interface, while simultaneously causing plastic flow of the metal material at the joining interface. The pressure applied when locally pressurizing the area to be joined is a pressure that can generate the aforementioned plastic flow and solid-state join the butt surfaces of the newly formed surfaces that appear due to the plastic flow. This pressure depends on the type and thickness of each metal material in the plate assembly, but is, for example, 110 MPa to 2000 MPa.
[0061] The joint structure obtained by the above manufacturing method is formed as a point joint, where the joint is a spot-like, point-like structure, due to localized pressure applied to the area to be joined. Furthermore, the formation of an IMC layer is suppressed at the joint interface between the titanium plate and the metal plate at this point joint, meaning that the proportion of IMC layers with a thickness of 1 μm or less is 50% or more.
[0062] At the point joint, the plate assembly consisting of a titanium plate and a metal plate is compressed in the thickness direction by a pair of electrodes, forming an indentation. In other words, at the point joint, the thickness of both the titanium plate and the metal plate is reduced.
[0063] The thickness of the titanium plate at the point joint is not particularly limited, but may be, for example, 70% or less, 65% or less, 60% or less, 55% or less, or 50% or less of the thickness of the base material. Alternatively, the thickness of the titanium plate at the point joint may be, for example, 10% or more, 15% or more, 20% or more, 25% or more, or 30% or more of the thickness of the base material.
[0064] The thickness of the metal plate at the point joint is not particularly limited, but may be, for example, 95% or less, 90% or less, 85% or less, 80% or less, 75% or less, or 70% or less of the thickness of the base material. Alternatively, the thickness of the metal plate at the point joint may be, for example, 10% or more, 15% or more, 20% or more, 25% or more, or 30% or more of the thickness of the base material.
[0065] Furthermore, in the joint structure of this embodiment, it is preferable that the maximum hardness within the joint region of the point joint at a depth of 0.05 mm from the joint interface of the titanium plates is 15% or more higher than the average hardness of the base material of the titanium plates.
[0066] Here, the depth position of 0.05 mm from the bonding interface of the titanium plate refers to a position inside the titanium plate that is 0.05 mm away in the thickness direction from the overlapping surface with the metal plate, i.e., the bonding interface. Furthermore, the horizontal direction refers to the virtual axis C that passes through the bonding center 4C of the point bonding portion 4 as shown in Figure 1 and extends in the thickness direction. L This refers to a direction perpendicular to the given direction. Furthermore, the joint region of a point joint refers to the horizontal region between the two joint ends 4E located furthest from the joint center in the joint interface of a point joint, i.e., the part where the titanium plate and the metal plate are in contact, in a cross-section obtained by cutting the joint structure to be measured along the plate thickness direction so as to pass through the joint center of the point joint.
[0067] In a joined structure, if the maximum hardness of the joint interface in the joint region of the titanium plate is 15% or more higher than the average hardness of the base material, when stress is applied to the joined structure, interfacial fracture can be suppressed, and fracture can occur in the softer outer periphery of the joint region or in the base material. In other words, even greater joint strength can be achieved.
[0068] Furthermore, the maximum hardness within the joint area of the point joint at a depth of 0.05 mm from the joint interface of the titanium plate described above may be 20% or more, 25% or more, or 30% or more relative to the average hardness of the base material of the titanium plate.
[0069] In a joined structure, to make the maximum hardness of the joint interface in the joint region of the titanium plate 15% or more higher than the average hardness of the base material, the heating temperature and pressure of the joint interface should be appropriately adjusted in the manufacturing method described above.
[0070] The maximum hardness within the joint area of the point joint and the average hardness of the titanium base material at a depth of 0.05 mm from the joint interface of the titanium plates can be measured as follows.
[0071] <Methods for measuring various hardness levels of titanium plates> First, the joint structure to be measured is cut along the thickness direction, passing through the center of the point joint, to reveal the cross-section of the joint structure. In this cross-section, the Vickers hardness (HV) within the joint area of the point joint at a depth of 0.05 mm from the joint interface of the titanium plate is measured at 0.1 mm intervals, and the maximum value is taken as the maximum hardness (HV) of the above area.
[0072] Furthermore, in the cross-section of the above-mentioned joint structure, the Vickers hardness of the titanium plate base material portion located outside the above-mentioned area, where there are no other joints nearby and no processing has been applied, is measured at the center of the plate thickness for 2 mm (21 points in total), and the average value is taken as the average hardness (HV) of the base material.
[0073] Each of the above Vickers hardness values shall be measured according to the method specified in JIS Z 2244:2009 "Vickers hardness test - Test method".
[0074] Furthermore, in the joint structure of this embodiment, it is preferable that at the joint interface between the titanium plate and the metal plate at the point joint, one of the metal materials, either the titanium plate or the metal plate, protrudes 50 μm or more into the other metal material.
[0075] Here, Figure 3 is an optical microscope image of a cross-section of a jointed structure, which is an example of this embodiment. In the jointed structure shown in Figure 3, at the joint interface between the titanium plate and the steel plate (an example of a metal plate) at the point joint, the metallic material of the titanium plate (titanium-based metallic material) protrudes approximately 70 μm into the metallic material of the steel plate.
[0076] Thus, at the joint interface of a point joint, if one of the metal materials, the titanium plate or the metal plate, protrudes by 50 μm or more into the other metal material, when stress is applied to the joint structure and cracks propagate, the cracks tend to propagate along the protruding surface of the metal material. However, because the direction of crack propagation does not coincide with the direction in which the joint interface extends (horizontal direction), interfacial fracture is suppressed, and even greater joint strength can be achieved.
[0077] In addition, while either the titanium plate or the metal plate may protrude, it is preferable that the titanium plate protrudes from the metal plate, as shown in the joint structure in Figure 3, because the direction in which the crack propagates and the direction in which the joint interface extends are more likely to be misaligned.
[0078] Furthermore, while the overhang of the titanium plate or metal plate should be 50 μm or more, it may be 60 μm or more, 70 μm or more, or 80 μm or more, as this increases the likelihood of the direction in which the crack propagates and the direction in which the bonding interface extends.
[0079] In order to cause one of the metal materials, either the titanium plate or the metal plate, to protrude 50 μm or more into the other metal material at the joint interface of the point joint, the heating temperature and pressure of the joint interface should be appropriately adjusted in the above-described manufacturing method.
[0080] The amount of protrusion of the titanium plate or metal plate can be measured as follows.
[0081] <Method for measuring the overhang of titanium plates or metal plates> In the same manner as the <method for measuring the ratio of the IMC layer having a thickness of 1 μm or less> described above, the joint structure to be measured is cut, the cross section thereof is polished and etched, and then this cross section is observed using a SEM as an observation surface. From the enlarged image of the observation surface obtained by SEM, taking the straight line connecting the two joint end portions 4E at the joint interface of the spot joint portion, that is, the two joint end portions 4E located on the farthest side from the joint center in the portion where the titanium plate and the metal plate are in contact with each other, as a reference line, the distance (length) between the apex of the protruding portion of the titanium plate or the metal plate and the reference line is measured. Then, the measured value is defined as the protrusion amount (μm) of the titanium plate or the metal plate.
[0082] Further, in the joint structure 1 of the present embodiment, a resin may be interposed between the titanium plate 2 and the metal plate 3 as long as the effects of the present invention are not impaired. When a resin is interposed between the titanium plate 2 and the metal plate 3, the current conduction path during energization can be controlled, the heat generation mode can be controlled as desired, and more favorable joining can be achieved. In addition, the resin functions as a sealing material for the joint interface, and by isolating the spot joint portion from the external environment during use, corrosion of the spot joint portion can be suppressed. Even if the spot joint portion is not completely isolated from the outside by the resin, if even a part of it is isolated, the effect of improving corrosion resistance can be obtained.
[0083] In the present embodiment, the resin to be interposed between the titanium plate and the metal plate is not particularly limited as long as it can function as described above, and may be any type of structural adhesive, any type of sealing material, or a resin plate or sheet.
[0084] Examples of the structural adhesive include reinforced epoxy, flexible epoxy, acrylic resin, reinforced acrylic resin, urethane resin, and silicone. In some cases, structural adhesives that can be used as sheets or films can be used. Furthermore, pressure-sensitive structural adhesives such as tapes can also be used.
[0085] Examples of sealants include silicone-based, silylated acrylate-based, modified silicone-based, polysulfide-based, acrylic urethane-based, polyurethane-based, acrylic-based, and butyl rubber-based sealants, as well as oil-based caulking materials and silicone mastic.
[0086] Furthermore, any known resin can be used for the resin plates or sheets. Specific examples of resins for resin plates and sheets include polyester resin, vinyl resin, polyurethane resin, epoxy resin, polyamide resin, polyimide resin, silicon resin, phenolic resin, melamine resin, urea resin, aniline resin, ionomer resin, and polycarbonate resin. The shape of the resin plates or sheets is not particularly limited; any shape that allows for control of the electrical path, such as having irregularities, holes, or a mesh structure, or a shape that can isolate it from the outside world, is acceptable.
[0087] Furthermore, when the resin interposed between the titanium plate and the metal plate is applied by coating, the coating method can be any form as long as it allows for control of the electrical path or provides a shape that can be isolated from the outside world. For example, the resin may be applied uniformly between the materials, applied only to a part near the joint point, applied only directly below the joint point, or applied so that it is not present directly below the joint point but only around it.
[0088] (Examples of application) As described above, the joint structure of the present invention allows for the simple manufacture of joint structures between titanium plates and metal plates other than titanium, even when the thickness ratio is large. It also exhibits excellent joint strength. Therefore, the present invention can be suitably used in various structures such as tanks, reaction vessels, and distillation columns in seawater desalination plants and chemical plants, or in offshore structures, where excellent corrosion resistance and durability are required.
[0089] The joint structures of the present invention are not limited to the embodiments described above, and can be appropriately combined, substituted, or modified without departing from the purpose and spirit of the present invention. In this specification, ordinal numbers such as "1st," "2nd," etc., are used to distinguish the items to which they are assigned, and do not indicate the order, priority, importance, etc. of each item. [Explanation of symbols]
[0090] 1 Jointed structure 2 Titanium plates 3 metal plate 4 point joint 4C Joint center 4E Joint end 51 1st electrode 52 2nd electrode
Claims
1. A joint structure between a titanium plate and a metal plate other than titanium, The aforementioned joint structure has point joints between the titanium plate and the metal plate, The thickness of the metal plate is four times or more the thickness of the titanium plate. A jointed structure characterized in that, at the joint interface between the titanium plate and the metal plate at the point joint, the proportion of intermetallic compound layers with a thickness of 1 μm or less is 50% or more.
2. The joint structure according to claim 1, characterized in that, at a depth of 0.05 mm from the joint interface of the titanium plate, the maximum hardness within the joint region of the point joint is 15% or more higher than the average hardness of the base material of the titanium plate.
3. The joint structure according to claim 1 or 2, characterized in that the thickness of the titanium plate is 2.0 mm or less.
4. The joining structure according to claim 1 or 2, characterized in that at the joining interface, one of the metal materials, either the titanium plate or the metal plate, protrudes into the other metal material by 50 μm or more.
5. The joining structure according to claim 1 or 2, characterized in that a resin is interposed between the titanium plate and the metal plate.
Citation Information
Patent Citations
Method for joining titanium sheet with steel sheet
JP1995266058A
Joining structure and joining method of steel and titanium plate
JP4216980B2
Method for joining metal materials
JP7526404B2